The Study on Thermal Environment and Airflow Pattern in an UFAD System Under a Cooling Mode - Yau, Yat Huang; Chuah, Keng H.; Siew, M.T. (Springer, 2020)
In the present research, an investigation of the UFAD system for thermal comfort has been conducted in a high-rise building located in the tropics. The indoor air conditions including temperature, relative humidity, air velocity, and mean radiant temperature have been obtained by conducting the fieldwork while the clothing insulation value and the metabolic rate of the occupants have been obtained by observing the occupants, where these data were used to obtain the predicted mean vote (PMV) and the predicted percentage dissatisfied (PPD) of the examined areas. In addition, the effects of the airflow pattern in the indoor thermal comfort have been investigated, where two different types of diffusers have been compared in order to find out which diffuser can provide a better thermal comfort to the occupants. The FloEFD simulation software is used to simulate the airflow pattern of these diffusers and to analyze the indoor air conditions of the UFAD system and also to examine the local mean age value. Based on the results obtained, the average PMV is approximately − 1.5 for each examined area, where a proper design of heating, ventilation, and air-conditioning system in a hot and humid country, the PMV result should be approximately equal to − 1. As for the PPD, the range of the PPD obtained falls in between 27.4 and 67.5%, in which it indicates that about more than half of the occupants have dissatisfied with the indoor conditions in the examined building. © 2019, King Fahd University of Petroleum & Minerals.